Physical explanation for vibro-acoustic modulation due to local and global nonlinearities in a structure and its experimental and numerical validation. (23rd June 2022) - Dorendorf, Lennart; Lalkovski, Nikolay; Rutner, Marcus
Abstract: This article introduces a simple physical explanation that demonstrates why a local or global nonlinearity in a structure causes amplitude modulation and phase modulation in the system response, when employing the vibro-acoustic modulation method for structural health monitoring (SHM) applications. The underlying major assumption and the explanation itself are validated experimentally and numerically. Afterwards, the explanation is used to demonstrate comprehensively why very different types of envelope functions can be observed in the system response, depending on the exciting ultrasonic carrier frequency ω . The beauty of the suggested explanation is that it does not only work for local nonlinearities, such as exhibited by defects, but also for any non-damage induced (local or global) nonlinearity in the system which can cause modulation as well. A physical understanding of cause and effect is of crucial importance here, because the modulation caused by non-damage induced nonlinearities might camouflage the effects of local damage that one is actually interested in during SHM applications. Highlights: Analytical physical explanation for vibro-acoustic modulation (VAM) Experimental and numerical validation of physical explanation Any local or global nonlinearity causes amplitude and phase modulation Explanation for different envelope functions in SHM-applications with VAM Identification of non-damage induced nonlinearities causing modulation